Bonding and Reactivity in Terminal versus Bridging Arenide Complexes of Thorium Acting as ThII Synthons. Issue 9 (18th January 2023) - Hsueh, Fang‐Che; Rajeshkumar, Thayalan; Kooij, Bastiaan; Scopelliti, Rosario; Severin, Kay; Maron, Laurent; Zivkovic, Ivica; Mazzanti, Marinella
Abstract: Thorium redox chemistry is extremely scarce due to the high stability of Th IV . Here we report two unique examples of thorium arenide complexes prepared by reduction of a Th IV ‐siloxide complex in presence of naphthalene, the mononuclear arenide complex [K(OSi(O t Bu)3 )3 Th(η 6 ‐C10 H8 )] (1 ) and the inverse‐sandwich complex [K(OSi(O t Bu)3 )3 Th]2 (μ‐η 6, η 6 ‐C10 H8 )] (2 ). The electrons stored in these complexes allow the reduction of a broad range of substrates (N2 O, AdN3, CO2, HBBN). Higher reactivity was found for the complex 1 which reacts with the diazoolefin IDipp=CN2 to yield the unexpected Th IV amidoalkynyl complex 5 via a terminal N‐heterocyclic vinylidene intermediate. This work showed that arenides can act as convenient redox‐active ligands for implementing thorium‐ligand cooperative multielectron transfer and that the reactivity can be tuned by the arenide binding mode. Abstract : A mononuclear arenide complex and an inverse‐sandwich complex of thorium can perform multielectron reductive chemistry with a range of substrates acting as Th II synthons. The mononuclear complex shows higher reactivity towards an diazoolefine yielding a Th IV amidoacetylido complex via a vinylidene intermediate suggesting that the Th reactivity is tuned by the arenide binding mode.